Mechanism of supply chain coordination based on price discount with privacy protection in one-supplier-one-buyer system - Xie, Cui-Hua; Zhan, Jing-Chun; Zeng, Le-Tian; Han, Shao-Yong (Frontiers in Physics, 2023)
It is of great economic significance to optimize the total cost and improve the performance of the supply chain. In this paper, we assume that the market demand is random, and the seller and the buyer share information and make decisions together. We analyze the optimal joint order quantity under probabilistic demand and design the quantity discount model and profit distribution mechanism. Under a certain quantity discount mechanism and profit distribution strategy, both the seller and the buyer can reduce costs. The quantity discount model and profit distribution mechanism designed require supply chain members to share information. In order to protect the privacy of members and improve the willingness of supply chain members to share information, we designed a privacy protection joint ordering policy protocol and privacy protection quantity discount policy based on SMC technology. Then, the joint ordering strategy, the privacy-preserving joint ordering strategy, and quantity discount protocol are numerically simulated. The numerical simulation results show that the privacy-preserving quantity discount coordination mechanism designed by us can reduce the cost of supply chain members to varying degrees and effectively protect the shared information of supply chain members. This work is helpful to the research of cost optimization of the system in complex supply chain systems.